Pendekatan Manajemen Pendidikan dalam Konsep Pendidikan Lingkungan Berbasis Nilai-Nilai Islam - Loviana, Shelvia; Gasmi, Nur Muhammad; Oktaviana N, Shella; Kasturi, Rima; Nuroni, Muhammad Amin; Junaidah, Junaidah (AL-IDARAH: JURNAL KEPENDIDIKAN ISLAM, 2024)
Environmental education in schools is a strategic step to raise students' awareness of the importance of preserving and protecting the environment. This study discusses the fundamental concepts of environmental education through the stages of planning, implementation, and evaluation in schools. Planning is carried out using a SWOT analysis to identify existing strengths, weaknesses, opportunities, and threats. The implementation phase includes the formation of a school environmental committee, determination of vision and mission, integration of programs into the curriculum, and collaboration with external parties. Evaluation aims to measure the effectiveness of the programs and provide feedback for further development. The results of this study indicate that structured environmental education can increase students' awareness and participation, as well as engage the entire school community in maintaining environmental quality. Thus, the implementation of environmental education in schools plays a crucial role in fostering a generation that is more environmentally conscious and committed to sustainability.